2023
DOI: 10.1097/pts.0000000000001103
|View full text |Cite
|
Sign up to set email alerts
|

Control Charts Usage for Monitoring Performance in Surgery: A Systematic Review

Abstract: Objectives:The control chart is a graphical tool for data interpretation that detects aberrant variations in specific metrics, ideally leading to the identification of special causes that can be resolved. A clear assessment of control chart utilization and its potential impact in surgery is required to justify recommendations for its dissemination. This review aims to describe how performance monitoring using control charts was used over time in surgery.Methods: A systematic search of PubMed regarding statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown clear advantages in adjusting models comparatively to non-risk-adjusted tools [ 28 ] using validation methodologies similar to ours [ 25 , 26 ]. A systematic review found that half of studies using control charts in surgery considered outcomes adjustment [ 6 ]. However, adjustment is complex and requires caution with the employed methodology and data [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown clear advantages in adjusting models comparatively to non-risk-adjusted tools [ 28 ] using validation methodologies similar to ours [ 25 , 26 ]. A systematic review found that half of studies using control charts in surgery considered outcomes adjustment [ 6 ]. However, adjustment is complex and requires caution with the employed methodology and data [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To deal with these methodological challenges, considering time-related proxies such as secular and seasonal trends could be of particular interest when tracking surgical safety. In past control chart literature, these variables were not identified as critical for surgical outcomes adjustment [ 6 ]. Secular trends reflect enhancing or deteriorating outcomes over years nationwide under the influence of a myriad of drivers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reported that the number of studies using control charts to monitor performance in the context of surgery has steadily grown over the last two decades. 18 Although some of these studies have focused on economic indicators, including length of stay and costs, none evaluated the economic effects of implementing a control chart-based programme for surgeon performance monitoring. In fact, the majority either aimed to adapt control chart methodology and test the utility or feasibility of their application in surgical departments, or used control charts to 6.5) Data are presented as numbers (percentage) of patients unless otherwise indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Original research measure the impact of quality improvement efforts in surgical departments. 18 Past research has suggested that reducing hospital bed-days after surgery could benefit healthcare systems by increasing hospital bed turnover. This can alleviate pressure on hospital staff and liberate beds to match demand with capacity for interhospital transfers, intensive care unit care and emergency admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation